Obesity among Pff-reserve First Nations, Métis, and Inuit Peoples in Canada’s Provinces: Associated Factors and Secular Trends - Ng, Carmina
Aboriginal Canadians (First Nations, Métis, and Inuit) have the highest prevalence of overweight and obesity compared to other ethnic groups in Canada. In order to assess the evolution of the problem over time and to understand potential risk factors, three studies were conducted using nationally-representative survey data. Direct comparisons between Aboriginal and non-Aboriginal Canadians from the same surveys provide important perspectives on the magnitude of health disparities that cannot be obtained by small regional studies that dominate the current available literature. Body mass index (BMI) trajectories from 1994 to 2009 were estimated for Aboriginal and non-Aboriginal Canadians. Aboriginal Canadians experienced higher rates of BMI increase over the 14-year period between 1994 and 2009. Rate of BMI increase was specifically higher for Aboriginal adults born in the 1960s and 1970s when compared with non-Aboriginal adults, and later-born cohorts had consistently higher BMI compared with earlier-born cohorts. The role of potentially modifiable lifestyle factors in obesity among Aboriginal and non-Aboriginal youth was also investigated. Compared to non-Aboriginal youth, consumption of fruits/vegetables and dairy products was lower, and more Aboriginal youth were "high" TV watchers. Physical activity participation did not differ between "high" and "low" TV watchers for both groups, and was associated with lowered odds for obesity only among Aboriginal youth. The complex relationship between obesity and socioeconomic status for Aboriginal and non-Aboriginal Canadians was explored. Employment status was strongly and negatively associated with obesity among Aboriginal men and women. Aboriginal men of high socioeconomic status (SES) were most likely to be obese, whereas Aboriginal women of high SES were least likely to be obese. Important descriptive and analytical information on an emerging and serious public health issue among Aboriginal people in Canada can inform the design and planning of intervention programs and development of public health strategies targeted at obesity. PhD